Sulphur immobilization and availability in soils assessed using isotope dillution - Nziguheba, Generose; Smolders, E.; Merckx, Roel (Elsevier, 2005)
Increasing recognition of S deficiency in soils has raised the need for understanding processes governing S cycling and availability in soils. However, the quantification of the two main processes of S cycling, i.e. mineralization and immobilization, remains difficult as these processes occur simultaneously. A modified isotope 35SO4 dilution technique was developed and used to measure the effect of sulphate (SO4) fertilization on S mineralization and immobilization in planted (pot experiment with ryegrass (Lolium multiflorum L.)) and unplanted soils (incubation). The immobilization and mineralization of S was calculated from the dynamics of stable and labelled S in soil KH2PO4 extracts containing an anion exchange membrane that concentrates SO4 and mainly excludes other S species. The mathematical analysis of the isotope dilution data differs from methods proposed earlier. The radiolabile S in unplanted soil (E value) and in ryegrass (L value) were used as a measure of total available S in soils. Sulphate immobilization rate significantly declined during incubation. Sulphate application reduced gross mineralization but surprisingly reduced SO4 immobilization. The E value significantly increased during the incubation in all soils as a result of gross mineralization, e.g. from 3.8 mg S kg−1 at day 0 to 11.5 mg S kg−1 at day 43 in the sandy soil with no sulphate addition. A full recovery in the E value of S added in (+S) treatments was achieved. Similarly, radiolabile S in the above-ground ryegrass biomass (L value) increased with S addition, with a full recovery of added S. The E and L values nearly fit a 1:1 line suggesting identical S dynamics in a planted and unplanted soil. The method proposed has operational advantages compared to methods used earlier.